The Analysis Of Ultrasonic Sensors In Smart Trash Bin Technology Based On Arduino Nano Microcontroller - Wicaksono Pratama, Adam; Agus Harijono (Indonesian Journal Publisher, 2024)
Waste is an environmental problem that is increasing along with population growth and public consumption. To solve this problem, an automatic device that controls the opening and closing of the trash can without direct touch is developed using an Arduino Nano microcontroller, HC-SR04 ultrasonic sensor, VL53L0X LIDAR, and MG996R servo motor. This research aims to evaluate the responsiveness of the sensor in detecting objects, the effect of the interaction of distance, angle, and object thickness on the sensor response time and aims to determine the effect of garbage volume on the response time of the indicator LED light. The test was conducted using the experimental method of distance variation of 20 cm, 30 cm, 40 cm, and 50 cm; angle variation of 0°, 10°, and 20°; and thickness variation of 10 mm, 65 mm, and 120 mm. Data analysis using multiple linear regression research methods shows a P-Value of 0.409 for the ultrasonic sensor with ɑ of 0.05, if the P-Value > ɑ, then H0 is accepted and H1 is rejected which mean that there is no significant effect of the interaction between distance, angle, and thickness of the object on the response time of the trash can lid opening sensor.